Pedagogical Content Knowledge of Intern Students using Lesson Study and Open Approach - Boondee, Settawut; Thinwiangthong, Sampan (Dhammathas Academic Journal, 2023)
The purpose of this research was to analyze the pedagogical content knowledge of intern students who use lesson study and open approach. The target group was 3 intern students who were teaching practice in mathematics subjects for 7th-grade students on the topic of equations. The research instruments consist of 5 lesson plans on equations, field notes, a camcorder, an audio recorder, and a photo camera. The data were analyzed by analytic description. The research results were as follows: Intern students have pedagogical content knowledge including of (1) Content knowledge, they plan to create problem situations that are consistent with content and teaching materials, plan to use teaching materials for representing the real world to link to the mathematical world, predict students' ideas in problem solving, plan to identify the discussion points and the awareness of ideas as well as misunderstandings, (2) Pedagogical knowledge, they pose the problem situations by using teaching materials to represent the real world, observe student ideas used in solving problems, order of students' ideas for presentation, discuss the important ideas, connect the representation of the real world to the mathematical world, and select of teaching materials and representations, (3) Identify student difficulty, they found the student problem of equation and several ideas for solving problem, some students are still unable to connect mathematical language to mathematical symbols.